English language teachers’ conceptions of assessment - Muianga, Felizardo (Frontiers in Education, 2023)
This small-scale qualitative study investigated twelve secondary school English language teachers’ views about the new secondary school assessment policy and their conceptions of the purposes of assessment. The data were collected through in-depth interviews in Maputo, Mozambique. The findings suggest that most participants are unfamiliar with the policy. The participants hold different conceptions of assessment. While some participants hold pure conceptions of assessment (i.e., improvement or student accountability), others hold mixed conceptions (i.e., mixed accountability and improvement and mixed student accountability and irrelevant).